A Systematic Review of Studies Comparing Actigraphy Indices in Patients with Depression and Schizophrenia - Ramdas Ransing; Pradeep Patil; Anurag Khapri; Aditya Mahindru (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Abnormalities in sleep-wake activities are frequently observed among patients with depression and schizophrenia. These abnormalities are variable and may have discriminative, clinical, diagnostic, and therapeutic significance if measured objectively with actigraphy. Aim: To systematically review the published literature on actigraphy in depression and schizophrenia, particularly to identify areas of research that need to be addressed before their clinical application in practice. Materials and Methods: The electronic databases (PubMed and Google Scholar) were searched for studies using the the key terms ‘actigraphy’ OR ‘actigraphic recording’ OR ‘wrist actigraphy’ OR ‘actometer’ OR ‘actimeter’ OR ‘actical’ OR ‘actiwatch’ OR ‘sleep-watch’ AND ‘schizoaffective’ OR ‘schizophr*’ OR ‘psychosis’ AND ‘depression’ OR ‘depressive’ in title and abstract. The literature search was limited to articles published in English and until 31st December, 2020. Data were abstracted by two reviewers and presented as a narrative summary of the findings. A qualitative synthesis of the study designs, populations, and outcomes was conducted. The quantitative synthesis of the results was not possible to conduct due to the heterogeneity and scarcity of the included studies. Results: Out of 33 searched articles, a total of four studies (three observational and one case report) were included for the review. The included studies were heterogeneous, small in sample size, divergent in methods, inclusive of clinical population, having more than two groups (depression, schizophrenia, mania, or bipolar disorders), and with a low degree of evidence. Overall, the patients with schizophrenia have more structured and less complex activity pattern than those with depression. Furthermore, the patients with schizophrenia showed more irregular patterns in the morning period and increased fluctuations inactivity in the evening period than depression patients. Conclusion: Currently, available information is insufficient to draw firm conclusions on use of actigraphy indices (e.g., duration of active periods, a pattern of activity, and sleep) for diagnosis and discrimination among the patients with schizophrenia and depression. Large, prospective, and comparative studies are required to identify role of actigraphy among these patients.